Becoming arts education researchers through a poetic collaborative self-study - Caetano, Ana Paula; Paz, Ana Luísa (European Public & Social Innovation Review, 2025)
Introduction: In a collaborative project involving teachers and students of a PhD in arts education, a poetic self-study was carried out to problematize the learning processes of becoming researchers in this field of study. Methodology: The paper focuses on the experiences of the researchers-educators, recorded in their diaries, by analysing and debating topics and research methodologies, but also their learning. The poetic and collaborative nature of this inquiry is emphasized through the presence and cross-referencing of narratives, visual essays and poetic writings. Results: Becoming researchers in arts education is a complex and a never-ending task. In this project teachers are researchers of their own processes of becoming teachers and researchers, and the results are the presentation of the several layers of productions they made. Discussions: All the experiences that researchers live are experiences to be questioned, interpreted, reinvented through reflection, writing, dialogue. Arts become modes of inquiry, of teaching and of creative production. Conclusions: Becoming researchers is, therefore, experiencing theory in practice, expanding knowing by arts creation and fruition, inventing and proposing research situations to reflect in and on action.